If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + -1x)(4 + -1x) = 0 Multiply (6 + -1x) * (4 + -1x) (6(4 + -1x) + -1x * (4 + -1x)) = 0 ((4 * 6 + -1x * 6) + -1x * (4 + -1x)) = 0 ((24 + -6x) + -1x * (4 + -1x)) = 0 (24 + -6x + (4 * -1x + -1x * -1x)) = 0 (24 + -6x + (-4x + 1x2)) = 0 Combine like terms: -6x + -4x = -10x (24 + -10x + 1x2) = 0 Solving 24 + -10x + 1x2 = 0 Solving for variable 'x'. Factor a trinomial. (4 + -1x)(6 + -1x) = 0Subproblem 1
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {4, 6}
| x(12-2x)(8-2x)=0 | | x^2+xy-2y^2+x-11y-12=0 | | 3c+14=5c | | 21x/52 | | 6x+8=10x-4 | | X-18/2=5X | | 4a+2e=70 | | r^2-12+w+3wr-4tr= | | 4d^-4e^-1/2f^-4 | | 2x^3-5x^2-12x+27=0 | | 4x-5-2x=13 | | 5/8-2/4= | | 4/7a=14 | | 15-1/3x=14 | | 12-81= | | 4e+2a=1 | | 5x^2+3t-4=2t-1 | | 3y+10=3y+20 | | 64X^3+16X^2+4X-3=0 | | 4(X+3x)=58 | | 3p=6181-2q | | x/4-4/5=19/20 | | 2x-(x-5)=6-(x+1) | | 3p-3=27 | | 4(x-5)=6+2(x+3) | | 10x^2-9x-1368=0 | | q+100=400 | | 8x-14=7x+26 | | n(n-3)=7*(4) | | 13lnx=15 | | 28m=7 | | 5a+2(a-4)=27 |